Arthroscopic assessment in acute ankle fractures - Reinaldo de Sousa Moreira Pinto , Zaira; Almeida de Sousa Nogueira , Thomás; de Almeida Miranda, Vitor; de Sousa, Eduardo Branco (Journal of the Foot & Ankle, 2025)
Objective: The goal of the present study is to carry out an inventory of intra-articular injuries through arthroscopy in patients with ankle fractures. Methods: An observational cross-sectional study was performed evaluating 28 patients who underwent an ankle before and after ankle osteosynthesis. Six items were evaluated: medial malleolus reduction, intra-articular loose bodies, osteochondral lesion, lateral ligament, and deltoid integrity. Results: The sample included 12 (42.86%) male patients and 16 (57.14%) female patients, aged around 45.7 years. Out of 28 fractures, 20 were Danis Weber type B. Intra-articular lesions of the ankle were found in 24 patients. A total of 17 (60.71%) patients had syndesmotic injuries and 16 (57.14%) had osteochondral lesions. Lateral and medial ligament injuries were found in five patients each. Medial malleolar fractures were identified in 12 patients, four of which were poorly reduced. Conclusion: Ankle fractures are commonly associated with intra-articular ankle fractures. Denis Weber type C fractures frequently present with severe osteochondral and ligamentous injuries. Level of evidence IV; Therapeutic studies; Case series.